Design, Synthesis, and Antifungal Activity of Novel 1,2,4-Triazolo[4,3-c]trifluoromethylpyrimidine Derivatives Bearing the Thioether Moiety - Liu, Chunyi; Fei, Qiang; Pan, Nianjuan; Wu, Wenneng (Frontiers in Chemistry, 2022)
Crop disease caused by fungi seriously affected food security and economic development. Inspired by the utilization of fungicide containing 1,2,4-triazole and trifluoromethylpyrimidine, a novel series of 1,2,4-triazolo[4,3-c]trifluoromethylpyrimidine derivatives bearing the thioether moiety were synthesized. Meanwhile, the antifungal activities of the title compounds were evaluated and most compounds exhibited obvious antifungal activities against cucumber Botrytis cinerea, strawberry Botrytis cinerea, tobacco Botrytis cinerea, blueberry Botrytis cinerea, Phytophthora infestans and Pyricutaria oryzae Cav.. Among the compounds, 4, 5h, 5o and 5r showed significant antifungal activities against three of the four Botrytis cinerea, which indicated the potential to become the leading structures or candidates for resistance to Botrytis cinerea.